Arabic dialect typology: Some significant isoglosses - Ould Mohamed Baba, Ahmed Salem (Anaquel de Estudios Árabes, 2010)
Recently, there has been a significant increase in research in Arabic dialectology. In spite of this, the literature on this subject has not yet elaborated a comprehensive system of dialect typologies. Based on the work of various specialists in this area, this article considers the diverse classifications made, as well as the criteria used, in dialectical geography of the Arab world to date. Considering these classifications imply the existence of differential characteristics, this work also advances the salient traits of the Arabic dialect areas.
Keywords: Arabic dialectology; Arabic dialect typology; Arabic dialect geography; Arabic dialect areas; Isoglosses